Assessment of milk handling practices and bacterial contaminations along the dairy value chain in Lushoto and Handeni districts, Tanzania - Shija, F. (2013)
Contaminated milk is responsible for up to 90% of all dairy-related diseases of humans. A cross sectional study was carried out in Lushoto and Handeni districts of Tanga, Tanzania to determine the milk handling practices, bacterial contamination and selected milk-borne zoonotic pathogens along the dairy value chain. A total of 93 respondents were interviewed and 184 milk and milk product samples were collected. Laboratory analysis of total and coliform plate counts, detection of Escherichia coli O157:H7 and Brucella abortus using polymerase chain reaction (PCR) were done. Results showed that, most farmers (57 %) milked their cows under unhygienic conditions. More than 60% of farmers did not clean their hands, wash cow teats and clean animal houses before milking. The majority (92.1%) of farmers were not trained on livestock keeping and milk handling. Although the mean TPC was within the East African Community (EAC) standards, general counts ranged between 3.3 to 5.8 log10. Eighty seven and 93% of milk from farmers and vendors, respectively, did not meet the TPC EAC standards. All the collected milk did not meet the CPC EAC standards, indicating contamination of milk with coliforms. PCR analyses did not detect E. coli O157:H7 in all the tested samples while B. abortus was detected in 37 out of 87 samples tested. It was concluded that unhygienic practices of milking and post-harvest handling along the dairy value chain possibly contributed to microbial contamination of milk. Detection of B. abortus in milk is of public health significance due to its zoonotic potential. It is recommended that veterinary/extension services be provided to livestock farmers on proper animal husbandry and control of zoonotic animal diseases. Public education should be given to all stakeholders in dairy industry on milking and post harvest handling of milk to curtail the likely losses due to rejection of spoiled milk and milk-borne pathogens resulting from contamination of milk.